A emergência da identidade ambiental territorial na agricultura familiar nos municípios de Santa Rosa e Novo Machado, RS - Godoy, Cristiane Maria Tonetto (2015)
Since the Industrial Revolution, economic development is based on the use of natural resources and non-renewable resources, causing socio-environmental impacts and the loss of biodiversity, creating problems for living beings as a whole. Faced with this problem, have raised debates about the need for environmental preservation and environmental sustainability as a guarantee of self-perpetuation and preservation of the human being. Thus, it is essential that work in all spheres, promoting dialogue and ways to get information from all parts of society, so therefore each individual create environmental awareness and promote the end of the degradation process environmental. In this work we study the emergence of the identification of the problem of construction and affirmation of "new" territorial identities based on ecological / environmental movement and the Brazilian environmental legislation, based on environmental concerns of contemporary society, setting the family farm as agent and stage multiple territories. For this, farmers were surveyed in the municipalities of Santa Rosa and Novo Machado, both in the state of Rio Grande do Sul, with the choice of properties those who were with permanent preservation areas (APPs) monitored and according to environmental legislation. As results we can infer that the construction of an environmental identity is possible from the existence of permanent protection areas normalized by environmental legislation. However, only the existence and recovery of the law does not ensure a change of perception and not the formation of environmental identity, in other words, that this identity be effective it is necessary that the application of the legislation is accompanied by an environmental education and access the information, which enables individuals to look critically at their actions, allowing the change of perception and consequently the scope of sustainability. Thus, we believe it is extremely important that you undergo studies and discussions on the construction of territorial identity and the identity of the territory based on environmental heritage and the importance of family farming in this context as active actors in the preservation of natural resources and the search for sustainability, enabling the territories constitute a development strategy for family farming and the countryside.